Quality of Life in Patient with Systemic Lupus Erythematosus (SLE) - Irma Yanih (Universitas Airlangga, 2016)
The number of patient with Systemic Lupus Erythematosus (SLE) was keep growing. SLE attacked many women and developed between the age of 15-45. The treatment which used by patient with SLE just for reduced or faded the symptoms that occurred. It couldn't heals the patient properly yet, so that sometimes that symptoms would occur again. The object of this study were to see the quality of life from 13 patient SLE in 8 domain from Quality of Life (QoL) such as physical health, emotional health, body image, pain, planning, fatigue intimate relationship and burden to others. This study was a study case in 13 patient with SLE which lived in Surabaya and a member of Lupus Indonesia Foundation branch Surabaya. Primary data were collected by interview using LupusQoL questionnaire and the weight was measured by digital weight scales. In this study, there were 13 woman patient with SLE in the age between 15-40 years old with highly educated and having normal nutrition status. They usually work and having monthly income > Rp 1,740,000, were suffer SLE for more than 5 years and having good knowledge in Lupus and SLE. This study showed a good value quality of life in patient with SLE at 3 domain. That were body image, intimate relationship and physical health domain. Some patients had a bad even worse quality in pain, fatigue and burden to others domain. Some of patients with SLE had a good quality of life except pain, fatigue, and burden to others domain. Keywords: Quality of Life (QoL), Systemic Lupus Erythematosus (SLE), desease duration